FRI0035 Expression and functions of vascular endothelial growth factor and angiopoietin receptors in human synovial mast cells. (23rd January 2014) - Rivellese, F.; Prevete, N.; Rossi, F.W.; Lamacchia, D.; Pelosi, C.; Marone, G.; de Paulis, A.
Abstract : Background: Mast cells accumulate in the synovial tissue of patients with rheumatoid arthritis (RA) and several data in murine models demonstrate that they can contribute importantly to the initiation of inflammatory arthritis. In fact, mast cell activation in the rheumatoid lesion provides numerous mediators, including histamine, heparin, proteinases, leukotrienes and multifunctional cytokines, that contribute to inflammatory and degradative processes, especially at sites of cartilage erosion. Little is known, however, about the factors responsible for mast cells accumulation in inflamed synovia. It is probable that Stem Cell Factor (SCF), the signature mast cell growth and differentiation factor and potent mast cell chemotaxin, plays a central role in regulating synovial mast cell trafficking. Indeed, the typical arthritic cytokine TNF induces expression and release of SCF by synovial fibroblasts, promoting mast cell chemotaxis. Among the other possible mediators, it is known that angiogenic factors are highly expressed in synovial fluids and sera of RA patients. Previous experimental data from our group support the hypothesis that vascular endothelial growth factors (VEGFs), although classically considered relatively endothelial-cell-specific factors, can activate immune cells through their receptors. Therefore we hypothesized that VEGF and angiopoietins could be responsible for mast cells accumulation in synovia. Objectives: We aimed to characterize the expression and functions of angiogenic receptors on human synovial mast cells (HSyMCs) to identify a non-immunological activation pattern implicated in mast cells recruitment in synovial tissue. Methods: We evaluated the expression of vascular endothelial growth factor receptors 1 and 2 (VEGFR-1 and VEGFR-2) and angiopoietin receptors (Tie1 and Tie2) mRNAs in human mast cells lines (LAD-2 and HMC-1) by RT-PCR. The surface expression of the receptors was then confirmed by Flow Cytometry on HSyMCs isolated by enzymatic digestion from synovial tissue obtained from patients undergoing synovectomy. Finally, we evaluated the effects of angiogenic factors on HSyMC chemotaxis using a Boyden chamber. Results: Human mast cells lines (LAD-2 and HMC-1) constitutively express mRNAs for VEGFR-1, VEGFR-2, Tie1 and Tie2. HSyMCs constitutively express on their surface VEGFR-1, VEGFR-2, Tie1 and Tie2. VEGF-A165 (50–500 ng/ml) induced HSyMCs chemotaxis with a potency similar to SCF. The chemotactic effects were mediated by the activation of both VEGFR-1 and VEGFR-2, as demonstrated by blocking experiments. We also observed that Ang1, but not Ang2, induced migration of HSyMCs through the engagement of Tie2. Conclusions: Our data indicate that HSyMCs are a target of angiogenic factors, which, in addition to the specific activation of endothelial cells, might play a wider role in inflammatory response in RA synovitis by activating immune cells. Here we also identify a non-immunological mechanism that accounts for the chemotactic activation of human synovial mast cells. References: de Paulis A, Prevete N, Fiorentino I, et al. Expression and functions of the vascular endothelial growth factors and their receptors in human basophils. J Immunol 2006;177:7322-31 Nigrovic PA, Lee DM. Synovial mast cells: role in acute and chronic arthritis. Immunol Rev 2007;217:19-37 Disclosure of Interest: None Declared